Management of Electronic Health Records in Virtual Health Environments: The Case of Rocket Health in Uganda - Masenya, Tlou M.; Ssekitto, Francis; Kaddu, Sarah; Simati, Sam (International Journal of Healthcare Information Systems and Informatics, 2024)
This article examined the management of electronic health records in virtual health environments using rocket health as a case study. The specific objectives of the study were to determine the healthcare services provided at rocket health; examine the electronic health records management practices adhered to at rocket health; and determine the inhibitors to effective electronic health records management at rocket health. A case study with a mixed-methods research approach was used. Data was collected using questionnaires, document reviews and structured interviews. The study finds that rocket health provided a range of healthcare services encompassing telehealth, pharmacy, last mile delivery, and an online store. These services predominantly operated in a digital format, resulting in the generation of electronic health records (EHRs), and therefore to capture and maintain these EHRs from multiple service points, rocket health implemented a cloud-based system.